Effects of Antihypertensive Treatment on Platelet Function in Essential Hypertension - SHIBUYA, Yuko; NAGAO, Reiko; GOMI, Tomoko; IKEDA, Toshio (Hypertension Research, 2000)
To evaluate the effect of antihypertensive therapy on platelet activation in essential hypertension, the plasma levels of β-thromboglobulin (β-TG) were examined in 45 patients with essential hypertension and 20 age-matched normotensive control subjects. Hypertensive patients were assigned to monotherapy with one of five different antihypertensive drugs for 6 months, and the change of plasma levels of β-TG was reexamined after the completion of the monotherapy. The plasma β-TG increased in hypertensive patients ompared with levels in normotensive control subjects. Monotherapy with each drug resulted in sufficient blood pressure control in all hypertensive patients. The plasma β-TG decreased significantly after monotherapy with an α-blocker or an angiotensin-converting enzyme inhibitor (ACEI). The plasma β-TG increased with the use of a diuretic but did not change with the use of a β-blocker or calcium antagonist. The platelet activation observed in patients with essential hypertension is reversed by monotherapy with an α-blocker or an ACEI. It is possible that these drugs reduce the development of hypertensive vascular complications due to suppression of platelet activation in patients with essential hypertension. (Hypertens Res 2000; 23: 567-572)